Simulação numérica da convecção mista em cavidade preenchida com meio poroso heterogêneo e homogêneo - Tavares, Renato Normandia (2016)
In this work is presented mixed convection heat transfer inside a lid-driven cavity heated from below and filled with heterogeneous and homogeneous porous medium. In the heterogeneous approach, the solid domain is represented by heat conductive equally spaced blocks; the fluid phase surrounds the blocks being limited by the cavity walls. The homogeneous or pore-continuum approach is characterized by the cavity porosity and permeability. Generalized mass, momentum and energy conservation equations are obtained in dimensionless form to represent both the continuum and the pore-continuum models. The numerical solution is obtained via the finite volume method. QUICK interpolation scheme is set for numerical treatment of the advection terms and SIMPLE algorithm is applied for pressure-velocity coupling. Aiming the laminar regime, the flow parameters are kept in the range of 102≤Re≤103 and 103≤Ra≤106 for both the heterogeneous and homogeneous approaches. In the tested configurations for the continuous model, 9, 16, 36, and 64 blocks are considered for each combination of Re and Ra being the microscopic porosity set as constant φ=0,64 . For the pore-continuum model the Darcy number (Da) is set according to the number of blocks in the heterogeneous cavity and the φ. Numerical results of the comparative study between the microscopic and macroscopic approaches are presented. As a result, average Nusselt number equations for the continuum and the pore continuum models as a function of Ra and Re are obtained.